1995
DOI: 10.1164/ajrccm.152.2.7633736
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests in HIV-infected patients without AIDS. Pulmonary Complications of HIV Infection Study Group.

Abstract: To determine the prevalence, incidence, and types of lung diseases that occur in association with HIV infection, 1,353 subjects, including HIV-seropositive homosexual men, injection drug users, female sexual partners of HIV-positive men, and HIV-seronegative control subjects from the first two transmission categories were evaluated prospectively in a multicenter study. Patients with AIDS at the time of initial evaluation were excluded. One thousand two-hundred ninety-four subjects who had no AIDS-defining diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 8 publications
7
41
0
1
Order By: Relevance
“…Before combination ARV, lung function impairment was worse with more advanced HIV disease, and similar to our study, abnormally low diffusing capacity was the most prominent finding (31,32). The DL CO % predicted in pre-ARV cohorts of HIVinfected outpatients was somewhat higher than in our cohort (78.5-84.8% vs. 72.3%) and was associated with cigarette smoking, IV drug use, CD4 cell count, PCP, and Kaposi sarcoma (7,8,(32)(33)(34). Although we also found an association of diffusing capacity with smoking and IV drug use, we did not find an independent association with CD4 cell count and none of our subjects reported a history of Kaposi sarcoma.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Before combination ARV, lung function impairment was worse with more advanced HIV disease, and similar to our study, abnormally low diffusing capacity was the most prominent finding (31,32). The DL CO % predicted in pre-ARV cohorts of HIVinfected outpatients was somewhat higher than in our cohort (78.5-84.8% vs. 72.3%) and was associated with cigarette smoking, IV drug use, CD4 cell count, PCP, and Kaposi sarcoma (7,8,(32)(33)(34). Although we also found an association of diffusing capacity with smoking and IV drug use, we did not find an independent association with CD4 cell count and none of our subjects reported a history of Kaposi sarcoma.…”
Section: Discussionsupporting
confidence: 89%
“…The only study in the combination ARV era found a lower prevalence of overall symptoms (31.5%), but was performed in a younger cohort with a lesser smoking history (12). Prior studies have also documented a high prevalence of abnormalities in spirometry and diffusion (8,31,32). Before combination ARV, lung function impairment was worse with more advanced HIV disease, and similar to our study, abnormally low diffusing capacity was the most prominent finding (31,32).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Inspiratory muscle dysfunction is related to the severity of HIV infection. 16,20 The present data reveal that 55% of HIVinfected patients presented IMW in a sample of clinically stable patients. This finding is compatible with previous studies.…”
Section: Discussionmentioning
confidence: 49%